Increasing Financial Efficiency and Employee Performance through Work From Home - Work From Office Work Method Implementation Strategies: A Conceptual Framework for Future Research Agenda - Suyono, Joko; Alimudin, Arasy; Elisabeth, Damarsari Ratnasahara; Sukaris, Sukaris; Darmayanti, Novi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aims to investigate the impact of integrating Work From Home (WFH) and Work From Office (WFO) work methods on organizational financial efficiency and employee performance. The study employs a systematic literature review methodology to synthesize relevant theoretical frameworks and empirical evidence. The findings reveal that the strategic implementation of WFH-WFO integration can lead to significant improvements in both financial efficiency and employee performance. Key determinants of successful implementation include robust technological infrastructure, managerial support, and a conducive organizational culture. Theoretical implications highlight advancements in organizational theories, behavioral theories, and management theories, while managerial implications underscore the importance of strategic planning, investment in technological infrastructure, cultivation of organizational culture, promotion of employee well-being, training and development initiatives, and performance measurement and evaluation. Overall, this research provides actionable insights for organizations seeking to optimize financial efficiency and employee performance through the strategic integration of WFH-WFO work methods.